Characterization of the host–guest complex of a curcumin analog with β-cyclodextrin and β-cyclodextrin–gemini surfactant and evaluation of its anticancer activity - Poorghorban M (Dove Medical Press, 2015)
Masoomeh Poorghorban,1 Umashankar Das,2 Osama Alaidi,1 Jackson M Chitanda,2 Deborah Michel,1 Jonathan Dimmock,1 Ronald Verrall,3 Pawel Grochulski,1,4 Ildiko Badea1 1Drug Discovery and Development Research Group, College of Pharmacy and Nutrition, 2Department of Chemical and Biological Engineering, 3Department of Chemistry, University of Saskatchewan, Saskatoon, SK, Canada; 4Canadian Light Source, Saskatoon, SK, Canada Background: Curcumin analogs, including the novel compound NC 2067, are potent cytotoxic agents that suffer from poor solubility, and hence, low bioavailability. Cyclodextrin-based carriers can be used to encapsulate such agents. In order to understand the interaction between the two molecules, the physicochemical properties of the host–guest complexes of NC 2067 with β-cyclodextrin (CD) or β-cyclodextrin–gemini surfactant (CDgemini surfactant) were investigated for the first time. Moreover, possible supramolecular structures were examined in order to aid the development of new drug delivery systems. Furthermore, the in vitro anticancer activity of the complex of NC 2067 with CDgemini surfactant nanoparticles was demonstrated in the A375 melanoma cell line.Methods: Physicochemical properties of the complexes formed of NC 2067 with CD or CDgemini surfactant were investigated by synchrotron-based powder X-ray diffraction, Fourier-transform infrared spectroscopy, and thermogravimetric analysis. Synchrotron-based small- and wide-angle X-ray scattering and size measurements were employed to assess the supramolecular morphology of the complex formed by NC 2067 with CDgemini surfactant. Lastly, the in vitro cell toxicity of the formulations toward A375 melanoma cells at various drug-to-carrier mole ratios were measured by cell viability assay.Results: Physical mixtures of NC 2067 and CD or CDgemini surfactant showed characteristics of the individual components, whereas the complex of NC 2067 and CD or CDgemini surfactant presented new structural features, supporting the formation of the host–guest complexes. Complexes of NC 2067 with CDgemini surfactants formed nanoparticles having sizes of 100–200 nm. NC 2067 retained its anticancer activity in the complex with CDgemini surfactant for different drug-to-carrier mole ratios, with an IC50 (half-maximal inhibitory concentration) value comparable to that for NC 2067 without the carrier.Conclusion: The formation of host–guest complexes of NC 2067 with CD or CDgemini surfactant has been confirmed and hence the CDgemini surfactant shows good potential to be used as a delivery system for anticancer agents. Keywords: inclusion complex, supramolecular arrangement, small-angle X-ray scattering, powder X-ray diffraction, cytotoxic activity